A New Device Improves Signs and Symptoms of TMD - Ruggero Cattaneo; Davide Pietropaoli; Barry C. Cooper; Dino Capparè; Eleonora Ortu; Annalisa Monaco (Pain Research and Management)
Background. Temporomandibular joint dysfunction (TMD) therapy remains an open challenge for modern dentistry. Herein, we propose a new neuromuscular lingual device able to reduce signs and symptoms of TMD in female patients with chronic orofacial pain. Methods. 50 females with myofascial TMD according to RDC/TMD were randomly assigned to study (n = 25) and control groups (n = 25). At T0, both groups received sEMG/KNG and pain evaluation by the VAS scale. The study group received the ELIBA device (lingual elevator by Balercia) constructed under ULF-TENS (ultra-low-frequency transcoutaneous electrical nervous stimulation). Subjects were instructed to use ELIBA at least for 16 h/day. After 6 months (T1), both groups underwent to sEMG/KNG and VAS revaluation. Results. T1 study group compared to controls showed a significant reduction in total (p<0.0001) and mean (p<0.0001) sEMG values, as well as a significant increase in both maximum vertical mouth opening (p=0.003) and maximum velocity in mouth opening (p=0.003) and closing (p<0.0001). Interestingly, a significant reduction in pain measured by VAS (p<0.0001) was reported. Conclusions. After 6 months, the ELIBA device is able to significantly reduce TMD-associated myogenous pain and to promote the enhancement of sEMG/KNG values. Practical Implications. ELIBA can be considered as a new device, potentially useful for head-neck pain relief in patients suffering from chronic TMD. In addition, its use promotes a muscles relaxation inducing freeway space increase. This characteristic makes it particularly useful for rehabilitation of patients with not enough space for construction of conventional orthotics or neuromuscular bites.